Prótese adesiva em resina fotopolimerizavel e fibra de vidro: uma alternativa social viável - relato de caso clinico - MAGALHÃES, Daniel Guilherme Borges (2018)
The main causes of dental loss are dental caries, periodontal disease, lack of acces to dental care, or trauma. Metal-ceramic prosthesis have been used for many years in dental practice. They demand more tooth wear during preparation and have laboratory costs involved, that may not be accessible to all patients. Therefore, adhesive prosthesis reinforced by fiber glass are a social temporary alternative for those patients who desire minimal tooth wear, and can not afford a conventional metal-ceramic prosthesis. The patient came to the dental clinic complaining of the absence of tooth 15. After criterious analysis of x-ray exams, all treatments availables were offered to the patient, who denied them because he could not afford the costs involved. Afterall, the patient was offered an adhesive prothesis to solve his problem temporarily. Plaster models were obtained using alginate (Jetralte – Dentsply) and plaster type IV and III (Herodent). Dental preparations were made with a dental bur number 3131. Provisional prosthesis was made using self-curing acrylic resin. Final molding was done with condensation silicon (Dentsply) using the putty-wash technique and retractor cord. The cast models were obtained using plaster type IV and III (Herodent). The confection of the adhesive prosthesis was done with a fiber post White Post DC 1 (FGM), Interlig (Angelus), Resina Opallis (FGM), Resina Opus (FGM).